2010 IEEE Virtual Reality Conference (VR) 2010
DOI: 10.1109/vr.2010.5444804
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Experience Test: A virtual environment evaluation questionnaire

Abstract: We present the development and evaluation of the Virtual Experience Test (VET). The VET is a survey instrument used to measure holistic virtual environment experiences based upon the five dimensions of experiential design: sensory, cognitive, affective, active, and relational. Experiential Design (ED) is a holistic approach to enhance presence in virtual environments that goes beyond existing presence theory (i.e. a focus on the sensory aspects of VE experiences) to include affective and cognitive factors.To e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 24 publications
1
26
0
2
Order By: Relevance
“…As a consequence, better performances can be achieved (Barfield et al 1995). The enhancement of the sense of presence theorized in Chertoff et al (2008) was experimentally confirmed in the study reported in Chertoff et al (2010).…”
Section: Experiential Designsupporting
confidence: 52%
See 2 more Smart Citations
“…As a consequence, better performances can be achieved (Barfield et al 1995). The enhancement of the sense of presence theorized in Chertoff et al (2008) was experimentally confirmed in the study reported in Chertoff et al (2010).…”
Section: Experiential Designsupporting
confidence: 52%
“…Table 1 (middle column) reports the five dimensions of ED applied toward VEs, as illustrated in Chertoff et al (2010). By designing a holistic experience in which all these dimensions are integrated, a user can fill the information not provided by the VE by recalling his previous experience.…”
Section: Experiential Designmentioning
confidence: 99%
See 1 more Smart Citation
“…For the Media Area, we reviewed previous studies regarding the evaluation of VR media [9,12,[17][18][19][20]. We also broadly reviewed evaluation indices, such as the Igroup Presence Questionnaires (IPQ) [21], Flow State Scale [22], Suitability Evaluation Questionnaire (SEQ) [23], Virtual Experience Test [24], and the User Satisfaction Evaluation Questionnaire (USEQ) [25]. Based on this review, we drew up six evaluation items for the Media Area-Sensory Immersion, Usability, (Media) Satisfaction, Manipulability, Navigability, and Presence.…”
Section: E Evaluation Areas Of Vr Training Contentsmentioning
confidence: 99%
“…Web based interactive virtual educational environment is an important method that can be used to replace the off-line education. Rapid technological advances are prompting Web contents to make a transition from 2D to 3D in order to enhance satisfaction for the users [1][2][3][4][5]. Recently, research works on Web 3D based e-learning system for healthcare education have also been extensively conducted [6][7][8].…”
Section: Introductionmentioning
confidence: 99%